Composition of Energy Drink Samples in Bangladesh - Alam Refat, Md Reazul; Nandi, Polash; Shoeb, Mohammad; Sultana, Abida (Dhaka University Journal of Science, 2022)
The commercial energy drink samples of 10 different brands were analyzed to study the level of alcohol (if any), sodium benzoate, caffeine, vitamin B, and carbohydrates content. Samples were degassed by ultrasonicator, and CO2 was found to be in a range of 1.27 ± 0.05 to 4.10 ± 0.10 mL per 100 mL sample. The amount of caffeine, sodium benzoate, glucose, and vitamin B were studied by a UV-Visible spectrophotometer. The wavelength of absorption maxima was 224, 272, 489, 445, and 292 nm, respectively, for sodium benzoate, caffeine, glucose, vitamin B2, and vitamin B6. The correlation coefficients of the calibration curves were found to be 0.998, 0.992, 0.998, 0.997, and 0.989 for caffeine, glucose, sodium benzoate, vitamin B2 and vitamin B6, respectively. The alcohol content was studied by gas chromatography equipped with a flame ionization detector. Ethanol was not found to be present in any sample. The caffeine and sodium benzoate content in different samples was found in the range of 147.84 ± 0.53 to 846.78 ± 2.64 and 52.92 ± 6.23 to 1575.37 ± 4.99 μg/mL, respectively. The sugar content in different samples was found to be 16.16 ± 4.25 to 338.33 ± 0.75 mg/mL. Vitamin B2 was found to be 13.21± 0.08 and 1.04 ± 0.002 μg/mL, respectively in Bacchus and Wild Brew samples and Vitamin B6 was found to be 261.17 ± 8.38 and 115.88 ± 0.31 μg/mL in Red Bull and Bacchus samples, respectively. The pH of the samples was found to be in the range of 2.79 ± 0.04 to 4.88 ± 0.04. Dhaka Univ. J. Sci. 70(1): 42-48, 2022 (January)